Synthesis of serving policies for objects flow in the system with refillable storage component - Fedosenko, Yuriy S.; Miroshina, Anastasia S.; Pudov, Andrey S.; Plekhov, Aleksandr S.; Chakirov, Roustiam; Houlden, Nigel (2017 Internet Technologies and Applications (ITA), 2017)
This paper discusses the solution of the logistic problem occurred in a management system to supply fuel to inhabitants in the Arctic regions using bulk water transport delivery. The suggested mathematical model of a logistic scheme is designed in the form of uniprocessor system with refillable storage component providing a single stage service of deterministic objects flow. The task scheduling optimisation problem is formulated in the way where service policies are estimated by two independent minimised criteria. Proposed synthesis algorithm of Pareto-efficient service policies utilises a bicriterial approach of dynamic programming. The algorithm has been verified by the simulation example.